Analisis Efektivitas Sistem Berbasis Data Penjualan dan Penyediaan Barang - Masyita Risna; Nurkhalik Wahdanial Asbara; Nurul Istiqamah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This study aims to analyze the effectiveness of a data-based system in the areas of sales and inventory provision at Master Stokist Takalar of PT Mega Gloryoung International (MGI). The study employed a mixed-method approach by integrating qualitative and quantitative data. Primary data were obtained through interviews, observations, and questionnaires administered to 20 respondents, while secondary data were collected from sales reports, transaction records, and inventory data. Quantitative analysis was conducted using descriptive statistics through effectiveness percentages and efficiency comparisons, whereas qualitative analysis was carried out through data reduction, data display, and conclusion drawing. The findings indicate that the data-based system is effective in the sales aspect, as reflected by an average effectiveness rate of 89%, reduced time required for transaction recording, data retrieval, and report preparation, as well as a 12% upward trend in sales. However, in the inventory provision aspect, the system’s effectiveness has not yet been optimal because stock management is still conducted manually, stock monitoring is not yet real-time, and demand forecasting remains reactive. These conditions indicate that the effectiveness of the system at Master Stokist Takalar is still partial, being strong in sales transactions but weak in inventory control. Therefore, stronger integration between the sales system and the inventory system is necessary to enhance distribution stability and reduce the risk of stockouts